Synthesis, Spectroscopic and Electrochemical Studies of Cobalt(II) and Nickel(II) Macrocyclic Complexes Derived from Oxalodihydrazide and Aldehydes/Propanone - Rai, H.C.; Sharma, Annapurna; Sharma, Meera; Kumari, Sarita (Asian Journal of Chemistry, 2010)
Synthesis of 14-membered macrocyclic complexes of cobalt(II) and nickel(II) of the type [M(mac1-3)] are reported. The complexes have been characterized on the basis of analytical, metal conductivity, magnetic susceptibilities, infrared, electronic, spectral data and electrochemical studies. Infrared spectral data show that the ligands behave in a diabasic tetradentate manner in all the complexes. Electronic spectral data and magnetic moment value are indicative of square planar geometry. The nickel complexes were red or orange to yellow in colour, whereas cobalt(II) complexes were chocolate brown in colour. High dilute conditions were maintained to dispense with polymerization reaction. The thermodynamic parameters E1/2 are found within the range -1.34 to -1.50 V.